The doughnut whodunit eaudiobook - Warner, Gertrude Chandler (The Boxcar Children, 2018)
A hip new doughnut shop known for its bizarre recipes is opening up in Greenfield. At first, the owners of the other doughnut shop in town, Delilah's, aren't worried. Their shop has been a fixture downtown since just after World War II. But when the new shop starts making doughnuts that look just like some of Delilah's greatest hits, the Boxcar Children must figure out if it's just a coincidence or if someone from the new shop is stealing Delilah's recipes.